Poincaré Plot Is Useful for Distinguishing Vasovagal Syncope From Postural Tachycardia Syndrome in Children - Yuan, Piaoliu; Lian, Zhouhui; Wang, Yuanyuan; Wang, Yaru; Zhang, Chunyu; Du, Junbao; Huang, Yaqian; Liao, Ying (Frontiers in Pediatrics, 2022)
Objectives: To explore the role of the Poincaré plot derived from a 24-h Holter recording in distinguishing vasovagal syncope (VVS) from postural tachycardia syndrome (POTS) in pediatric patients. Materials and Methods: Pediatric patients with VVS or POTS, hospitalized in Peking University First Hospital between January 2012 and December 2018, were included in a derivation study. The transverse axis (T), longitudinal axis (L), T/L ratio, product T×L, distance between the origin and the proximal end of the longitudinal axis (pro-D), and distance between the origin and distal end of the longitudinal axis (dis-D) of the Poincaré plot were compared between the VVS group and the POTS group, and the differential diagnostic performance of the above-mentioned graphic parameters was evaluated by receiver operating characteristic curve analysis. A validation study was conducted in pediatric patients hospitalized between January 2019 and December 2020. Results: In school-aged children, the T, L, T/L, T×L, and dis-D values of patients with VVS were greater than those of patients with POTS; in adolescents, the T, T/L, T×L, and pro-D values of patients with VVS were greater than those of patients with POTS. Using a T/L cut-off value of 0.3 to distinguish between the two diseases, the sensitivity and specificity were 91.0% and 90.5%, respectively, for the total participants; 91.6% and 88.9%, respectively, for the school-aged children; and 82.1% and 95.7%, respectively, for the adolescents. In the validation study, a T/L cut-off value of 0.3 yielded an accuracy, sensitivity, and specificity of 81.8%, 87.2%, and 77.6%, respectively, in the total participants; 76.5%, 82.6%, and 71.4%, respectively, in the school-aged children; and 89.2%, 93.8%, and 85.7%, respectively, in the adolescents, in distinguishing VVS from POTS validated by clinical diagnosis. Conclusions: The graphic parameters of the Poincaré plot are significantly different between VVS and POTS in pediatric patients, and the T/L of the Poincaré plot is a useful measure to differentiate VVS from POTS in children and adolescents.